The Theological Discourse on Divine Attributes - Ahmad Hisyam Syamil; Amir Reza Kusuma (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2026)
This study examines the theological perspectives on Divine Attributes among the Ashʿarī, Māturīdī, and, highlighting their doctrinal differences and methodological approaches. While the Ashʿarīs affirm Divine Attributes as neither identical to nor separate from God’s essence, the Māturīdīs emphasize rational-textual balance, rejecting anthropomorphism without negating attributes. In contrast, the Muʿtazilites deny eternal attributes, arguing they compromise God’s unity (tawḥīd), and interpret scriptural anthropomorphisms metaphorically. Employing a critical-analytical method, this research reveals how these schools navigate the tension between divine transcendence and scriptural literalism. The findings underscore the Ashʿarī-Māturīdī alignment against Muʿtazilite rationalism, while noting subtle divergences between them. The study contributes to broader Islamic theological discourse by clarifying these schools’ positions on Divine Attributes.